Interdyscyplinarny paradygmat "Childhood Studies" w perspektywie konstrukcjonizmu - Małgorzata Kowalik-Olubińska (Problemy Wczesnej Edukacji)
The author situates her deliberations within the area of the interdisciplinary research paradigm known as Childhood Studies. The subject of her interest is the application of the ideas of constructionism, the adoption of which played a vital role in the emergence of Childhood Studies as a separate field of studies. At the time of shaping and consolidation of the new paradigm, constructionism turned out to be the primary metatheory within it. The objective of the following article is to demonstrate the values and weaknesses of the entanglement of Childhood Studies in this theoretical perspective.